On the boundary element methods with Müller's formulation for electromagnetic scattering problems in periodic domains - Niino, Kazuki; Nishimura, Naoshi (Proceedings of 2013 URSI International Symposium on Electromagnetic Theory, 2013)
We investigate a boundary element method with Mϋller's formulation for dielectric scattering problems in periodic domains. In this method, the iteration number of iterative methods is expected to be small because the operators in Mϋller's formulation are the sum of bounded operators and compact operators. We use the Nystrom method for the discretisation so that we do not need to use any basis. We make several numerical experiments to see the accuracy and the efficiency of this method.